PENGARUH PENGETAHUAN KESEHATAN REPRODUKSI TERHADAP PERILAKU SEKSUAL PRA NIKAH PADA MAHASISWA AKPER DI YOGYAKARTA - Wiwi Kustio Priliana (MEDIA ILMU KESEHATAN, 2017)
Background: In Indonesia about 15% of adolescents aged 10-24 years have been having sex outside of marriage. Indonesian teenagers today are more tolerant of premarital sexual lifestyle. This is evident from the research results of various institutions in Indonesia during the period 1993-2002, found that 5-10% of women and 18-38% of young men aged 16-24 years have had premarital sexual relations with their age partner. Other research results also said that the cause of premarital sexual behavior in adolescents because of knowledge about reproductive health. Knowledge of reproductive health is considered taboo to be discussed. This is precisely pushing the knowledge of adolescent to sexual becomes more. Objective: Knowing the description of Akper students who have engaged in sexual behavior influenced by knowledge of reproductive health . Methods:This type of research is an observational study using cross sectional study design. Results: Students who have high reproductive health knowledge are more than 65,9% in mild prenatal sexual behavior. Students with low level of knowledge have a chance of having a mild pre-marital behavior 2 times higher than students with high knowledge of reproductive health. From the results of bivariable analysis, both variable a significant relationship with premarital sexual behavior with a value of p <0,05. Conclusion; Akper students who have premarital sexual behavior are 69.9%. They tend to engage in premarital sexual behavior then have a low reproductive health risk. Category of premarital sexual behavior includes holding hands, hugging, kissing dry (kissing the cheeks or forehead) and kissing wet (kissing the lips). Premarital sexual behavior is caused by high knowledge of reproductive health. Keyword: Premarital sexual behavior and knowledge of reproductive health